Geoquímica das rochas alcalinas máficas subaflorantes na zona urbana de Fortaleza – Ce - Werneck, Luiza Silva (2018)
The Cenozoic alkaline volcanism in Ceará State, specific at metropolitan region of Fortaleza, is represented by necks, plugs and domes of phonolites and trachytes, with rare described dikes of tephrites and phonotephrites. The new subsurface volcanic rock in Fortaleza is classified as a basanite strongly enriched by incompatible elements (Ba, Th, U, Ta, Nb, La e Ce), which is almost 400 by 320 meters in area and at least 20 meters of thickness. Geochemistry data and multivariate analysis show this occurrence is the mafic member of the Messejana Volcanism, which is in the continental prolongation of the Fernando Noronha Fracture Zone, indicating a bimodal character to this event. A comparison of Fernando de Noronha Volcanism samples, which had originated the namesake archipelago with ages between 12.5±0.1 e 1.3±0.1 My, and the study area data shows strong petrographic and geochemical resemblance among the both localities rocks. The magma which has originated this basanite shows strong REE fractionation pattern and Ce/YbN rate of 18,02 to 20,17, enriched in REEL, absent Eu anomaly. It also presents depletions of Sm, Eu, Tl, Tb, Y, and Yb, while shows enrichment of Cs and Rb, which could be related to the OIB pattern. However, Ba, Th and U enrichment and Sr and P depletion reveal crustal influence. Applying a multivariate analysis, such as Correspondence Analysis, to the geochemical data allow its interpretation in a reduced dimensional space, thus understanding the behavioral processes of individuals. This method indicated a strong geochemical similarity among Fortaleza and Fernando de Noronha basanites, such as higher values of Na2O, K2O, Al2O3, TiO2, P2O5 and CaO2, and smaller values of SiO2 e MgO relatively to those of Macau Volcanism. Trace elements like Rb, Nb, Th and Ga are correlated, and its values increase or diminish together on each volcanism, while Sr and Ba have an inverse behavior comparing to Cr and Ni.